Organizing Health Inequalities? Employee-Driven Innovation and the Transformation of Care. (March 2019) - Halford, Susan; Fuller, Alison; Lyle, Kate; Taylor, Rebecca
This article responds to calls for new approaches to understanding and intervening in health inequalities and, in particular, for attention to the processes and relations that mediate structural inequality and everyday outcomes. Our contribution focuses on the part that healthcare organizations play in this. We draw on organizational sociology, which theorizes that while organizational structures, cultures, and practices may appear neutral – and rely for their legitimacy on this – they may, in fact, operate in the interests of some social groups and less in the interests of others. This proposition is worked through new empirical research on employee-driven innovation in the UK National Health Service. In both our case studies, front-line staff working with some of the most vulnerable citizens had identified the organization of care as both part of the problem and – potentially – part of the solution. In tracing their efforts to change the organization of care, we learn more about what it might take to mobilize resources in support of those whose lives are most affected by health inequalities.